Global land-use and carbon emission implications from biochar application to cropland in the United States. (10th June 2020) - Dumortier, Jerome; Dokoohaki, Hamze; Elobeid, Amani; Hayes, Dermot J.; Laird, David; Miguez, Fernando E.
Abstract: Biochar has the potential to increase crop yields when applied to agricultural land. We integrate agronomic and economic simulation models to determine the expected yield increase from biochar applications in the United States. We calculate the location-specific willingness to pay of U.S. farmers to apply biochar to their cropland if biochar increases yields over 20 years. In addition to the potential benefit of higher revenue for farmers, biochar applications also have policy implications if biochar production is combined with bio-fuel production or used to reduce greenhouse gas emissions from indirect land-use change. Thus, the results are then combined with an agricultural outlook model to determine the effects on global land-use change and net carbon emissions. Our results indicate that biochar application is most profitable for croplands in the Southeast U.S. due to the combination of high yield increases and availability of biomass to produce biochar. An increase in U.S. yields above trend by 1% for corn, soybeans, and wheat would decrease net total global emissions by 25–87 Tg of CO2 -equivalent. Graphical abstract: Image 1 Highlights: Yield increases of 2.5%–12.7% above baseline from biochar application to cropland. Crop prices are main determinant for willingness-to-pay for biochar. Biochar adoption likely in the Southeast and Northeast due to high willingness-to-pay. Reduction in global crop area due to biochar-induced higher crop yields in the U.S. Potential for significant carbon credits for avoided indirect land-use change.